A panel data analysis of the formal-informal sector labour market linkages in South Africa. Issue 3 (4th May 2019) - Nackerdien, Faeez; Yu, Derek
ABSTRACT: This study explores the labour market linkages between the informal and formal sectors, using the first four waves of the National Income Dynamics Study data. The main focus is on three groups of employed: worked in the formal sector in all waves; worked in the informal sector in all waves; moved between the two sectors across the waves. Only 27% of informal sector workers in wave 1 transitioned to the formal sector in wave 4; 38% remained in the informal sector while 33% had their status changed to either inactive or unemployed. The econometric analysis indicates that older and more educated individuals living in urban areas and coming from households with fewer old-age grant recipients are significantly more likely to work in the formal sector, whereas more educated white males are associated with a significantly greater likelihood of transitioning from informal to formal sector employment.